Preparation method and application of high-adhesion adhesive for nuclide removal
By preparing high-adhesion adhesives, combined with polyvinyl alcohol, crosslinking materials and plant polyphenols, the problem of insufficient strength and adhesion in the removal of existing adhesives in nuclides was solved, and efficient nuclide removal on complex surfaces and micro-nano structures was achieved.
Patent Information
- Application Number
- CN202510632720.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-07-04
AI Technical Summary
Existing adhesives are difficult to adapt to complex surfaces and fine structures in nuclide removal, and cannot take into account high strength, high elasticity and high selectivity. They often lose adsorption efficiency and deformation ability in dry environments, limiting their application in extreme or special scenarios.
Polyvinyl alcohol is used as the substrate, combined with crosslinking materials, sodium benzoate, anionic surfactant, organic solvent and plant polyphenols, and high-adhesion adhesives are prepared through crosslinking reactions to enhance their mechanical strength and adhesion properties, and are prepared at room temperature to ensure environmental protection.
It significantly improves the comprehensive performance of the adhesive, can quickly and firmly adhere and embed radioactive particles, improves the efficiency and safety of nuclear pollution treatment, and is suitable for the removal of nuclides on complex surfaces and micro-nano structures.
Smart Images

Figure CN120248785A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive preparation, and in particular relates to a preparation method and application of a high-adhesion adhesive for nuclide removal. Background Art
[0002] With increasingly stringent environmental regulations and continuous advancement of new materials technology, adhesives, as a key functional material, are rapidly developing in the direction of green environmental protection, high performance and intelligence, especially in frontier fields such as nuclear safety, new energy, electronic manufacturing and sustainable development. They show great potential for application. For the efficient removal of radionuclides on the surface of objects, traditional physical and chemical methods, such as ultrasonic cleaning and conventional chemical detergents, are widely used, but they are difficult to meet the needs of deep decontamination of complex surfaces and fine structures. These traditional methods not only have limited adaptability to diverse substrates and low ability to adsorb and capture radionuclides, but also easily cause secondary pollution during use, posing a threat to the environment and human health, greatly restricting their effectiveness and promotion in high-standard nuclear safety scenarios.
[0003] In contrast, adhesives, relying on their excellent adhesion properties and high surface adaptability, can be evenly coated and tightly adhered to complex, irregular or even micro-nanostructured surfaces. Through physical adsorption and chemical bonding, they can effectively capture and fix radionuclide ions, greatly improving the interface with pollutants. This material not only shows significant radionuclide removal efficiency in practical applications, but also has the advantages of simple operation, low secondary pollution risk and good environmental compatibility. Therefore, adhesives are becoming a research and application hotspot in the field of surface radionuclide removal. However, currently commercially available or ordinary adhesives often only have good adsorption properties for a small number of specific radionuclides, making it difficult to adapt to the actual needs of nuclear safety and efficient purification. At the same time, they cannot take into account the organic unity of high strength, high elasticity and high selectivity. Problems such as loss of adsorption efficiency and deformation ability and low tensile strength often occur in dry environments, which greatly limits their wide application in extreme or special scenarios. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these objects and other advantages of the present invention, a method for preparing a high-adhesion adhesive for nuclide removal is provided, comprising the following steps:
[0006] Step 1: Pour 1-2 parts by weight of the cross-linking material into 100 parts by weight of warm water, and stir thoroughly until completely dissolved to prepare a cross-linking solution;
[0007] Step 2: Add 0.05 - 0.2 parts by mass of sodium benzoate, 2 - 8 parts by mass of an anionic surfactant, 1 - 10 parts by mass of an organic solvent, and 0 - 0.05 parts by mass of a pigment to 100 parts by mass of polyvinyl alcohol, and stir until the color is uniform to prepare a polyvinyl alcohol glue.
[0008] Step 3: Add 10 - 100 parts by mass of a crosslinking solution and 0.1 - 10 parts by mass of a plant polyphenol material to 100 parts by mass of the polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
[0009] Preferably, in the said Step 1, the crosslinking material is one or more of sodium tetraborate, boric acid, guar gum, ferric citrate, and sodium citrate.
[0010] Preferably, in the said Step 2, the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, sodium lauryl sulfate, sodium lauryl polyether sulfate, α-olefin sulfonate, secondary alkyl sulfonate, fatty alcohol sulfate, sodium stearate, potassium oleate, sodium xylene sulfonate, and alkyl phosphate ester salt.
[0011] Preferably, in the said Step 2, the organic solvent is one or more of propylene glycol, glycerol, triethyl citrate, tributyl acetylcitrate, epoxy soybean oil, glyceryl triacetate, poly(propylene glycol adipate), and sorbitol.
[0012] Preferably, in the said Step 3, the plant polyphenol is one or more of catechin, gallic acid, myricetin tannin, tannic acid, and lignan.
[0013] Preferably, the plant polyphenol used in Step 3 is modified by the following method:
[0014] S1: Immerse lignin fibers in a surfactant, filter out the lignin fibers and wash them clean after heat treatment, then add the lignin fibers and cellulase to water, react for a period of time and then filter out the lignin fibers, and wash them clean again to obtain pretreated lignin fibers.
[0015] S2: Disperse the plant polyphenol and the pretreated lignin fibers into water together, then adjust the pH with NaOH, add a crosslinking agent and heat to react for a period of time, filter and wash the product, and then dry it to obtain the modified plant polyphenol.
[0016] Preferably, in the said S1, the surfactant is a 1% solution of sodium lauroyl glutamate, heat it to 70 - 80 °C, carry out the heat treatment for 30 - 45 min, and the dosage ratio of lignin fibers, cellulase, and water is 1:0.02 - 0.04:100, and react for 1 - 2 h.
[0017] Preferably, in S2, the crosslinking agent is ethylene glycol diglycidyl ether, and the dosage ratio of the plant polyphenol, the pretreated lignin fiber, and the crosslinking agent is 1:0.1 - 0.2:0.02 - 0.05. Adjust the pH to 9 - 10, heat to 70 - 80 °C for treatment for 2 - 3 h, the drying temperature is 30 - 40 °C, and dry for 20 - 30 min.
[0018] The present invention also provides an application of the high - adhesion adhesive, using the adhesion adhesive to remove nuclides on the surface of an object.
[0019] The present invention has at least the following beneficial effects:
[0020] (1) The present invention uses polyvinyl alcohol as the base material, and synergistically introduces a cross - linking material, sodium benzoate, an anionic surfactant, an organic solvent, a pigment, and a plant polyphenol. The advantages of each component complement each other, significantly improving the comprehensive performance of the adhesive. Through the action of the cross - linking material, the mechanical strength and structural stability of the adhesive are greatly enhanced; sodium benzoate endows the adhesive with excellent anti - corrosion and anti - mildew capabilities, extending the storage and service life; the anionic surfactant effectively improves the dispersibility and wettability of the material, enhancing the wrapping and adhesion efficiency to the contaminated surface and nuclide particles; the selection of the organic solvent ensures the safety and environmental friendliness during the operation of the adhesive, the addition of the pigment facilitates the identification and management of the product, and the plant polyphenol further enhances the adhesion performance; the cooperation of each component endows the adhesive with excellent mechanical, durable, adhesive, anti - corrosion and other multiple functions.
[0021] (2) Compared with existing similar products, the materials used in the present invention are safe and green, and can be directly stirred and prepared at room temperature without high temperature or harmful solvents. The preparation process is simple, fast and energy - consuming, further improving the industrial and environmental friendliness. The high - adhesion adhesive shows higher safety and efficiency in radioactive pollution treatment scenarios such as nuclide removal, can quickly and firmly adhere to and embed radioactive particles, significantly improving the efficiency and safety level of nuclear pollution treatment, and has broad practical application prospects and promotion value. Description of the Drawings
[0022] Figure 1 It is the appearance diagram of the high - adhesion adhesive prepared in Example 1;
[0023] Figure 2 It is the appearance diagram of the high - adhesion adhesive prepared in Example 1 under the action of the palm;
[0024] Figure 3 It is the SEM image of the high - adhesion adhesive prepared in Example 1;
[0025] Figure 4 It is the stress - strain curve of the high - adhesion adhesive prepared in Example 1;
[0026] Figure 5 The peel strength of the highly adhesive adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2 after 20 adhesion-peeling cycles on pigskin.
[0027] Figure 6 The removal efficiency diagram of radionuclides on the surface of pigskin by the highly adhesive adhesive prepared in Example 1 and the materials prepared in Comparative Examples 1-2;
[0028] Figure 7 The removal efficiency diagram of radionuclides on the surface of pigskin by the highly adhesive adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2;
[0029] Figure 8 The removal efficiency diagram of radionuclides on the surface of pigskin by the highly adhesive adhesives prepared in Examples 1-7. Detailed implementation manners
[0030] The following further describes the present invention in detail with reference to the accompanying drawings and examples, so that those skilled in the art can implement it according to the description in the specification.
[0031] It should be understood that the terms such as "having", "comprising" and "including" used herein do not exclude the presence or addition of one or more other elements or their combinations.
[0032] Example 1
[0033] A preparation method of a highly adhesive adhesive for radionuclide removal, characterized by comprising the following steps:
[0034] Step 1: Pour 1 g of sodium tetraborate into 100 g of warm water, and stir thoroughly until completely dissolved to prepare a sodium tetraborate cross-linking solution;
[0035] Step 2: Add 0.05 g of sodium benzoate, 2 g of sodium dodecylbenzenesulfonate, 1 g of glycerol, and 0.01 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to prepare a polyvinyl alcohol glue;
[0036] Step 3: Add 10 g of the sodium tetraborate cross-linking solution and 0.1 g of myricetin tannin to 100 g of the polyvinyl alcohol glue in small amounts and multiple times, and stir rapidly each time until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
[0037] Figure 1 The appearance diagram of the highly adhesive adhesive prepared in Example 1; It can be seen through observation that the prepared highly adhesive adhesive can be designed in shape as needed, indicating its good plasticity;
[0038] Figure 2Appearance diagram of the highly adhesive adhesive prepared in Example 1 under the action of the palm; It can be seen through observation that the highly adhesive adhesive can produce arbitrary deformation under the action of the palm, indicating its good shape adaptability;
[0039] Figure 3 SEM image of the highly adhesive adhesive prepared in Example 1; It can be seen through observation that there is an obvious three-dimensional network structure inside the highly adhesive adhesive, which provides good support for the excellent mechanical properties and nuclide adsorption of the highly adhesive adhesive;
[0040] Figure 4 Stress-strain curve of the highly adhesive adhesive prepared in Example 1; It can be seen through observation that the maximum elongation rate and maximum tensile strength of the highly adhesive adhesive are 152.1% and 108.8 kPa respectively, indicating that the material has good resilience.
[0041] Example 2
[0042] A preparation method of a highly adhesive adhesive for nuclide removal, characterized by comprising the following steps:
[0043] Step 1: Pour 1.2 g of boric acid into 100 g of warm water, and stir well until completely dissolved to prepare a sodium tetraborate crosslinking solution;
[0044] Step 2: Add 0.1 g of sodium benzoate, 4 g of sodium lauryl sulfate, 3 g of triethyl citrate, and 0.02 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to prepare a polyvinyl alcohol glue;
[0045] Step 3: Add 30 g of boric acid crosslinking solution and 1 g of catechin to 100 g of polyvinyl alcohol glue in small amounts and multiple times, and stir rapidly each time until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
[0046] Example 3
[0047] A preparation method of a highly adhesive adhesive for nuclide removal, characterized by comprising the following steps:
[0048] Step 1: Pour 1.4 g of guar gum into 100 g of warm water, and stir well until completely dissolved to prepare a sodium tetraborate crosslinking solution;
[0049] Step 2: Add 0.15 g of sodium benzoate, 6 g of lauryl polyether sulfate, 5 g of tributyl acetylcitrate, and 0.03 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to prepare a polyvinyl alcohol glue;
[0050] Step 3: Add 50 g of boric acid cross-linking solution and 3 g of lignan into 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until the adhesive is formed and elastic, thus making a highly adhesive adhesive.
[0051] Example 4
[0052] A preparation method of a highly adhesive adhesive for nuclide removal, characterized by comprising the following steps:
[0053] Step 1: Pour 1.6 g of ferric citrate into 100 g of warm water and stir thoroughly until completely dissolved to make a sodium tetraborate cross-linking solution;
[0054] Step 2: Add 0.2 g of sodium benzoate, 8 g of α-olefin sulfonate, 5 g of epoxidized soybean oil, and 0.04 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to make polyvinyl alcohol glue;
[0055] Step 3: Add 70 g of boric acid cross-linking solution and 5 g of gallic acid into 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until the adhesive is formed and elastic, thus making a highly adhesive adhesive.
[0056] Example 5
[0057] A preparation method of a highly adhesive adhesive for nuclide removal, characterized by comprising the following steps:
[0058] Step 1: Pour 2 g of sodium citrate into 100 g of warm water and stir thoroughly until completely dissolved to make a sodium tetraborate cross-linking solution;
[0059] Step 2: Add 0.2 g of sodium benzoate, 8 g of secondary alkyl sulfonate, 9 g of glyceryl triacetate, and 0.05 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to make polyvinyl alcohol glue;
[0060] Step 3: Add 90 g of boric acid cross-linking solution and 9 g of ellagic acid into 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until the adhesive is formed and elastic, thus making a highly adhesive adhesive.
[0061] Example 6
[0062] A preparation method of a highly adhesive adhesive for nuclide removal, characterized by comprising the following steps:
[0063] Step 1: Pour 1 g of sodium tetraborate into 100 g of warm water and stir thoroughly until completely dissolved to make a sodium tetraborate cross-linking solution;
[0064] Step 2: Add 0.05 g of sodium benzoate, 2 g of sodium dodecylbenzenesulfonate, 1 g of glycerol, and 0.01 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to prepare polyvinyl alcohol glue.
[0065] Step 3: Modify myricetin tannin. The method is as follows:
[0066] S1: Disperse 10 g of myricetin tannin and 1 g of lignin fiber in water together, then adjust the pH to 9 with NaOH, add 0.2 g of ethylene glycol diglycidyl ether, heat to 70 °C and react for 2 h, filter and wash the product, and then dry at 35 °C for 25 min to obtain modified myricetin tannin.
[0067] Add 10 g of sodium tetraborate cross-linking solution and 0.1 g of modified myricetin tannin to 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
[0068] Example 7
[0069] A preparation method of a highly adhesive adhesive for nuclide removal, characterized by comprising the following steps:
[0070] Step 1: Pour 1 g of sodium tetraborate into 100 g of warm water, and stir thoroughly until completely dissolved to prepare a sodium tetraborate cross-linking solution.
[0071] Step 2: Add 0.05 g of sodium benzoate, 2 g of sodium dodecylbenzenesulfonate, 1 g of glycerol, and 0.01 g of pigment to 100 g of polyvinyl alcohol, and stir until the color is uniform to prepare polyvinyl alcohol glue.
[0072] Step 3: Modify myricetin tannin. The method is as follows:
[0073] S1: Immerse 10 g of lignin fiber in 100 mL of 1% sodium lauroyl glutamate solution, heat to 70 °C and treat for 40 min, then filter out the lignin fiber and wash it clean. Then add 10 g of lignin fiber and 0.2 g of cellulase to 1 L of water, react for 2 h, filter out the lignin fiber, and wash it clean again to obtain pretreated lignin fiber.
[0074] S2: Disperse 10 g of myricetin tannin and 1 g of pretreated lignin fiber in water together, then adjust the pH to 9 with NaOH, add 0.2 g of ethylene glycol diglycidyl ether, heat to 70 °C and react for 2 h, filter and wash the product, and then dry at 35 °C for 25 min to obtain modified myricetin tannin.
[0075] Add 10 g of sodium tetraborate crosslinking solution and 0.1 g of modified myricetin tannin to 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
[0076] Comparative Example 1
[0077] This comparative example provides a highly adhesive adhesive material, which is only different from Example 1 in that it does not add plant polyphenols (i.e., myricetin tannin). The preparation method includes the following steps:
[0078] Step 1: Pour 1 g of sodium tetraborate into 100 g of warm water and stir well until completely dissolved to prepare a sodium tetraborate crosslinking solution;
[0079] Step 2: Add 0.05 g of sodium benzoate, 2 g of sodium dodecylbenzenesulfonate, 1 g of glycerol, and 0.01 g of pigment to 100 g of polyvinyl alcohol and stir until the color is uniform to prepare a polyvinyl alcohol glue;
[0080] Step 3: Add 10 g of sodium tetraborate crosslinking solution to 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
[0081] Comparative Example 2
[0082] This comparative example provides a low-adhesion polymer material, which is mainly different from Example 1 in that it only has low adhesion. The preparation method includes the following steps:
[0083] Step 1: Pour 1 g of sodium tetraborate into 100 g of warm water and stir well until completely dissolved to prepare a sodium tetraborate crosslinking solution;
[0084] Step 2: Add 0.05 g of sodium benzoate, 2 g of sodium dodecylbenzenesulfonate, 1 g of glycerol, 10 g of acetic anhydride, and 0.01 g of pigment to 100 g of polyvinyl alcohol and stir until the color is uniform to prepare a polyvinyl alcohol solution;
[0085] Step 3: Add 10 g of sodium tetraborate crosslinking solution and 0.1 g of myricetin tannin to 100 g of polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time it is added until polymerization is formed and elastic to prepare a low-adhesion polymer material.
[0086] Application Example 1
[0087] Measurement of the peel strength of the highly adhesive adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2 after 20 adhesion-peel cycles on pigskin. The specific operation method is as follows: Before the test, the pigskin is heat-treated at 37 °C to simulate the human body temperature, and then the highly adhesive adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2 are respectively attached to the pigskin. In the experiment, a universal material testing machine is used to perform peel tests at a constant peel angle of 90° and a peel speed of 50 mm / min, and the peel force is recorded.
[0088] Figure 5 The peel strength of the highly adhesive adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2 after 20 adhesion-peel cycles on pigskin. From Figure 5 It can be seen that the adhesive materials prepared in Examples 1-5 and the adhesive material prepared in Comparative Example 1 have similar peel strengths, indicating that they have similar adhesion properties; while the peel strength of the polymer material prepared in Comparative Example 2 is much lower than that of other samples, indicating that it has relatively poor adhesion performance. This is because the introduced acetic anhydride converts some hydroxyl groups into hydrophobic groups.
[0089] Application Example 2
[0090] Measurement of the removal performance of the highly adhesive adhesives prepared in Examples 1-7 and the materials prepared in Comparative Examples 1-2 on radionuclides on the surface of pigskin. The specific operation method is as follows: The excised pigskin is cut into rectangular samples, and a rectangular pollution area of 5×5 cm 2 is defined, and the remaining part is kept clean for safe operation of the pigskin samples with tweezers. At the beginning of the experiment, 100 μL of uranium solution is quickly and evenly applied to the designated area of each sample using a pipette, and 50 μL is applied to each pigskin sample. After natural drying for a period of time, equal amounts of the adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2 are evenly applied to the surface of the pigskin. After acting for a period of time, the corresponding samples are removed, and then the remaining radioactive contamination level is measured.
[0091] Figure 6 The removal efficiency of the highly adhesive adhesive prepared in Example 1 and the materials prepared in Comparative Examples 1-2 on radionuclides on the surface of pigskin. From Figure 6 It can be seen that compared with Example 1, in Comparative Example 1, due to the absence of plant polyphenols and the lack of the chelating effect of plant polyphenols on radionuclides, the radionuclide removal efficiency of Comparative Example 1 decreases; in Comparative Example 2, due to the introduction of acetic anhydride converting some hydroxyl groups into hydrophobic groups, the adhesion of the material is reduced, so the radionuclide removal efficiency of Comparative Example 2 decreases; the radionuclide removal efficiencies of Comparative Example 1 and Comparative Example 2 decrease in turn, further indicating that the adhesion performance of the adhesive and the chelating effect of plant polyphenols can synergistically promote the removal of radionuclides on the surface and interface of the substrate.
[0092] Figure 7The nuclide removal efficiency of the highly adhesive adhesives prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-2 on the surface of pigskin. It can be seen from Figure 7 that the adhesive materials prepared in Examples 1-5 have similar nuclide removal efficiencies, indicating that the implementation schemes of the present invention have steady-state universality; while the nuclide removal performance of the polymer material prepared in Comparative Example 2 is much lower than that of the highly adhesive adhesive materials prepared in Examples 1-5 and Comparative Example 1, indicating that good adhesion performance design is one of the decisive factors for the nuclide removal effect on the substrate surface interface.
[0093] Figure 8 The nuclide removal efficiency of the highly adhesive adhesives prepared in Examples 1-7 on the surface of pigskin. It can be seen from Figure 8 that on the basis of Example 1, in Example 6, lignin fibers were used to modify plant polyphenols, so that plant polyphenols were grafted with lignin fibers containing phenolic hydroxyl groups, improving the chelating ability of plant polyphenols, and thus enhancing the nuclide removal efficiency; on the basis of Example 6, in Example 7, before grafting lignin fibers, they were pretreated to expose more phenolic hydroxyl groups, further enhancing the activity of lignin fibers, and thus improving the nuclide removal efficiency of plant polyphenols.
[0094] Although the implementation schemes of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation manners. It can be fully applied to various fields suitable for the present invention. For those familiar with the field, additional modifications can be easily achieved. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to the specific details and the examples shown and described here.
Claims
1. A preparation method of a high-adhesion adhesive for nuclide removal, characterized in that, It includes the following steps: Step 1: Pour 1-2 parts by mass of a crosslinking material into 100 parts by mass of warm water, and stir well until completely dissolved to prepare a crosslinking solution; Step 2: Add 0.05-0.2 parts by mass of sodium benzoate, 2-8 parts by mass of an anionic surfactant, 1-10 parts by mass of an organic solvent, and 0-0.05 parts by mass of a pigment to 100 parts by mass of polyvinyl alcohol, and stir until the color is uniform to prepare a polyvinyl alcohol glue; Step 3: Add 10-100 parts by mass of the crosslinking solution and 0.1-10 parts by mass of a plant polyphenol material to 100 parts by mass of the polyvinyl alcohol glue in small amounts and multiple times. Stir rapidly each time until the adhesive is formed and elastic to prepare a highly adhesive adhesive.
2. The preparation method of the highly adhesive adhesive for nuclide removal according to claim 1, characterized in that In the said Step 1, the crosslinking material is one or more of sodium tetraborate, boric acid, guar gum, ferric citrate, and sodium citrate.
3. The preparation method of the high-adhesion adhesive for nuclide removal according to claim 1, characterized in that, In the said Step 2, the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, sodium lauryl sulfate, sodium lauryl polyether sulfate, α-olefin sulfonate, secondary alkyl sulfonate, fatty alcohol sulfate, sodium stearate, potassium oleate, sodium xylene sulfonate, and alkyl phosphate ester salt.
4. The preparation method of the highly adhesive adhesive for nuclide removal according to claim 1, characterized in that In the said Step 2, the organic solvent is one or more of propylene glycol, glycerol, triethyl citrate, tributyl acetylcitrate, epoxidized soybean oil, triacetin, poly(propylene adipate), and sorbitol.
5. The preparation method of the high-adhesion adhesive for nuclide removal according to claim 1, characterized in that, In the said Step 3, the plant polyphenol is one or more of catechin, gallic acid, myricetin tannin, tannic acid, and lignan.
6. The preparation method of the high-adhesion adhesive for nuclide removal according to claim 1, wherein, Modify the plant polyphenol used in Step 3. The method is as follows: S1: Immerse lignin fibers in a surfactant, filter out the lignin fibers after heat treatment and wash them clean. Then add the lignin fibers and cellulase to water, react for a period of time and then filter out the lignin fibers, and wash them clean again to obtain pretreated lignin fibers; S2: Disperse the plant polyphenol and the pretreated lignin fibers together in water, then adjust the pH with NaOH, add a crosslinking agent and heat to react for a period of time, filter and wash the product, and then dry it to obtain a modified plant polyphenol.
7. The preparation method of the highly adhesive adhesive for nuclide removal according to claim 6, characterized in that, In the said S1, the surfactant is a 1% sodium lauroyl glutamate solution, heat up to 70-80 °C, heat treatment for 30-45 min, and the dosage ratio of lignin fibers, cellulase, and water is 1:0.02-0.04:100, and react for 1-2 h.
8. The preparation method of the high-adhesion adhesive for nuclide removal according to claim 6, wherein, In the said S2, the crosslinking agent is ethylene glycol diglycidyl ether, and the dosage ratio of the plant polyphenol, the pretreated lignin fibers, and the crosslinking agent is 1:0.1-0.2:0.02-0.05, adjust the pH to 9-10, heat to 70-80 °C and treat for 2-3 h, and the drying temperature is 30-40 °C, and dry for 20-30 min.
9. Use of a highly adhesive adhesive prepared by the preparation method according to any one of claims 1-8, characterized in that, Use the said adhesive to remove nuclides on the surface of an object.